Water-holding Capacity of Reclaimed Grassland with Different Ages in Karst Regions - Luo Xiulong; Shu Yingge; Long Hui; Li Xuemei (Shuitu baochi tongbao)
[Objective] The water-holding capacity of reclaimed grassland of different ages was studied in order to provide a scientific basis for water retention and soil and water conservation of reclaimed grassland in karst regions. [Methods] Reclaimed grassland of different ages (5, 10, 15, 20 yr) and cultivated land (CK) in a karst area in Anshui City, Guizhou Province was selected as the research objects, and the “space-time substitution method” was used to study litter storage, water-holding capacity, and water storage capacity. The change characteristics of soil profile bulk density, porosity, particle composition, water content, and water-holding capacity were determined for different ages of reclaimed grassland. [Results] ① The litter-layer storage capacity, maximum water-holding capacity, maximum storage capacity, and effective storage capacity followed the reclaimed grassland age order of 15 yr>20 yr>10 yr>5 yr. The relationships of litter-layer water-holding capacity and water absorption rate with soaking time were characterized by a logarithmic function and a power function, respectively. ② The sand content and bulk density of the reclaimed grassland showed a trend of first decreasing and then increasing as age of reclaimed grassland increased. Changes in silt, clay, total porosity, capillary porosity, maximum water-holding capacity, and capillary water-holding capacity were opposite to the changes in soil bulk density. ③ The total water-holding capacity of the litter layer and the soil layer followed the order of 10 yr>20 yr>15 yr>5 yr>CK. The maximum water-holding contribution rate of the soil layer was more than 99%. [Conclusion] Reclaimed grassland of different ages not only increased the bioaccumulation, rainfall interception, and water-holding capacity of the litter layer, but also improved soil structure and pore status. The soil water-holding capacity gradually stabilized after 10 years. Therefore, it is recommended that planting deciduous trees after 10 years of farmland conversion to grassland.